Experimental study of bias dependence of pulsed laser-induced single-event transient in SiGe HBT. (October 2016) - Sun, Yabin; Fu, Jun; Wang, Yudong; Zhou, Wei; Liu, Zhihong; Li, Xiaojin; Shi, Yanling
Abstract: This work presents a comprehensive investigation of single-event transient (SET) in SiGe HBT induced by pulsed laser irradiation at different bias conditions. The impacts of collector voltage V CC and base voltage V B on SET are compared and discussed. Experimental results show that SET in SiGe HBT highly depends on the applied bias conditions during irradiation. The underlying physical mechanisms are analyzed in detail. It is found that the variation of collector transient current approximately satisfies an ideal exponential discharge law. The additional discharge path plays a significant role in collector charge collection and discharge time constant once the transistors arrive at the reverse-active mode. Highlights: The effect of bias conditions on single-event transient were studied in SiGe HBT. SET highly depends on the applied bias condition during the plus laser irradiation. Ideal exponential discharge law is used to model the collector transient current. Additional discharge path plays vital role once transistor are in reverse-active mode.